Implementing the primary curriculum : a teacher's guide - Ashcroft, Kate; Palacio, David (Falmer Press, 1997)
Giving an overview of the whole of the curriculum, this book specifically identifies key features of the required and optional curriculum. The editors give practical examples for implementing new requirements into the teacher's daily workload.